Kedudukan Hukum Terhadap Pengguna Jasa Prostitusi Online Dalam Kitab Undang-Undang Hukum Pidana - Samsir, Samsir (Jurnal Penelitian Hukum Legalitas, 2025)
The use of social networks is not only a means of socializing and exchanging information but also an interactive medium, serving as a practical bridge for conducting business, providing services or social resources, and being utilized as a platform for engaging in illicit activities. Nowadays, social media has become a common and effective tool for achieving objectives in business affairs related to prostitution. This study employs the normative legal research method, which involves examining applicable laws and regulations or those implemented concerning a specific legal issue. In this context, the study analyzes the problem from the perspective of legal provisions on the criminal act of online prostitution. Based on various legal provisions in the Indonesian Penal Code (KUHP), Law No. 11 of 2008 on Electronic Information and Transactions, and Law No. 44 of 2008 on Pornography, the existing regulations have not been effective in prosecuting and combating the online prostitution business. These laws do not regulate the users of prostitution services, resulting in their exemption from legal prosecution under Indonesia’s Positive Law. Online prostitution refers to prostitution activities that use the internet as a medium for transactions. Under the Indonesian Penal Code (KUHP), only individuals who facilitate online prostitution, such as pimps or procurers, can be criminally prosecuted. Meanwhile, sex workers and their clients cannot be punished, as this offense is considered a victimless crime.